Paving the way towards the creation of a Euro-Mediterranean Innovation Space - Azzioui I. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
This article presents the rationale for including the innovation activities as part of the Euro-Med dialogue policy. It relies on an analysis focussed on the need to include innovation in the international cooperation schemes. It shows that policy can be largely upgraded to include not only simple measures aimed to promote international collaborations but more integrated joint initiatives targeted to encourage shared agendas and cooperative schemes. Finally the article indicates some general objectives for opening a dialogue process among Euro-Med science, technology and innovation stakeholders. The article gives the example of the conclusions of the MIRA forum on energy as a way to build this dialogue platform.